2022
DOI: 10.1002/14651858.cd013790.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Heated tobacco products for smoking cessation and reducing smoking prevalence

Abstract: Background Heated tobacco products (HTPs) are designed to heat tobacco to a high enough temperature to release aerosol, without burning it or producing smoke. They differ from e‐cigarettes because they heat tobacco leaf/sheet rather than a liquid. Companies who make HTPs claim they produce fewer harmful chemicals than conventional cigarettes. Some people report stopping smoking cigarettes entirely by switching to using HTPs, so clinicians need to know whether they are effective for this purpose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 86 publications
(10 reference statements)
4
38
0
1
Order By: Relevance
“…301 Under standing of exposure to e-cigarette smoke is growing, and it is now clear that vaping is harmful. Due to a lack of legislation and conflicting approaches to e-cigarette use in the medical field, 302 e-cigarettes and vapes can often be used in smoke-free areas and public confusion persists regarding their harmful effects.…”
Section: Inhalation Of Tobacco Drugs and Other Combustible Substancesmentioning
confidence: 99%
“…301 Under standing of exposure to e-cigarette smoke is growing, and it is now clear that vaping is harmful. Due to a lack of legislation and conflicting approaches to e-cigarette use in the medical field, 302 e-cigarettes and vapes can often be used in smoke-free areas and public confusion persists regarding their harmful effects.…”
Section: Inhalation Of Tobacco Drugs and Other Combustible Substancesmentioning
confidence: 99%
“…Current and former smokers reported that their perceptions of reduced harm were important in their decision to use IQOS, with most reporting concurrent IQOS and cigarette use 5. IQOS marketing asserts that switching completely from cigarettes to IQOS is necessary to obtain reduced toxicant exposure 7…”
Section: Introductionmentioning
confidence: 99%
“… 47 In addition, a Cochrane Review did not find any randomized controlled trials evaluating the effect of HTPs on cigarette smoking cessation, casting doubt on HTPs ability for this purpose. 48 Although the Hong Kong SAR Government has banned the import, manufacture, sale, distribution, and advertisement of alternative smoking products (ECs, HTPs, herbal cigarettes) on April 30, 2022, use of these products remain legal. 49 Smokers need better awareness of the risk of EC and HTP use to themselves and others, and their risk of addiction and relapse to cigarette use.…”
Section: Discussionmentioning
confidence: 99%